2018
DOI: 10.1002/aoc.4416
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a Cu‐MOF Nano‐Catalyst by using Post‐Synthetic Modification for the Preparation of 5‐Substituted 1H‐Tetrazoles

Abstract: A new nano scale Cu‐MOF has been obtained via post‐synthetic metalation by immersing a Zn‐MOF as a template in DMF solutions of copper(II) salts. The Cu‐MOF serves as recyclable nano‐catalyst for the preparation of 5‐substituted 1H‐tetrazoles via [3 + 2] cycloaddition reaction of various nitriles and sodium azide in a green medium (PEG). The post‐synthetic metalated MOF were characterized by FT‐IR spectroscopy, powder X‐ray diffraction (PXRD), atomic absorption spectroscopy (AAS), and energy dispersive X‐ray s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 82 publications
0
20
0
Order By: Relevance
“…The direct approach for synthesis of the Cu analog of CoFe 2 O 4 /Zn‐MOF (CoFe 2 O 4 /Cu‐MOF) by using CuCl 2 ·2H 2 O instead of Zn)NO 3 ) 2 ·6H 2 O was not successful . So, the metal‐exchange PSM was applied by using CoFe 2 O 4 /Zn‐MOF as template via immersing in DMF solution of CuCl 2 ·2H 2 O for 6 days at room temperature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The direct approach for synthesis of the Cu analog of CoFe 2 O 4 /Zn‐MOF (CoFe 2 O 4 /Cu‐MOF) by using CuCl 2 ·2H 2 O instead of Zn)NO 3 ) 2 ·6H 2 O was not successful . So, the metal‐exchange PSM was applied by using CoFe 2 O 4 /Zn‐MOF as template via immersing in DMF solution of CuCl 2 ·2H 2 O for 6 days at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The engineering of MM‐MOFs can lead to new frameworks with novel or multiple functions improving catalytic or gas sorption performance. Previous studies have shown the properties of several synthesized MM‐MOFs …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal–organic frameworks (MOFs), which are constructed via coordinating polytopic organic ligands with clusters or metal ions, have aroused tremendous attention in the fields of catalysis, gas adsorption and desorption,drug delivery and sensing, due to their unique features such as various functionalities, extensive surface areas, adjustable internal surface properties, and high regular pores …”
Section: Introductionmentioning
confidence: 99%
“…Over the past three decades, the synthesis of metal–organic frameworks (MOFs) as porous crystalline hybrid materials by assembling metal nodes and organic ligands has attracted considerable attention with the aim of finding meaningful applications in various fields such as gas storage and separation, drug delivery, optics, sensing and biomedical imaging . Due to the diversity in metal centres and functional groups, high surface area and tunable porosity, MOFs can be valid as versatile heterogeneous catalysts . Among various catalyst separation techniques in organic synthesis, a simple magnetic isolation process eliminates the requirement of catalyst filtration and centrifugation; so, MOFs based on a magnetic support provide easy manipulation.…”
Section: Introductionmentioning
confidence: 99%